2007
DOI: 10.1097/01.prs.0000279143.66781.9a
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Mammography following the Treatment of Primary Breast Cancer with Breast Reconstruction: A Systematic Review

Abstract: This study has demonstrated the paucity of evidence and highlighted the need for further research to evaluate this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 42 publications
(55 reference statements)
0
20
0
6
Order By: Relevance
“…53,54,56,59,60 Only six studies reported data on numbers of patients experiencing IBTR and/or MCBC events. [53][54][55][56][57][58] The paucity of the underlying evidence base mirrors the findings of previous reviews 4,29,[43][44][45][46][47] described earlier. Nevertheless, a number of conclusions may be drawn.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…53,54,56,59,60 Only six studies reported data on numbers of patients experiencing IBTR and/or MCBC events. [53][54][55][56][57][58] The paucity of the underlying evidence base mirrors the findings of previous reviews 4,29,[43][44][45][46][47] described earlier. Nevertheless, a number of conclusions may be drawn.…”
Section: Discussionmentioning
confidence: 48%
“…It is unclear which of these alternative methods of organising a service represent the most effective and efficient regimen. Previous systematic reviews 4,29,[43][44][45][46][47] have been unable to clarify the optimal frequency and duration of surveillance mammography.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 54 (24%) patients who presented with symptoms relating to breast reconstructions (most commonly lump or swelling), one-half were subsequently found to have no significant abnormality and one-third (29%) were found to have fat necrosis. Only four recurrences were found (105). Presently, assessment with ultrasound and mammography can only be supported in symptomatic patients, with surgical referral the most efficient means of obtaining a diagnosis while minimizing unnecessary tests or biopsies (106).…”
Section: What Is the Appropriate Post-breast Reconstruction Survmentioning
confidence: 99%